Connectivity of hydrology between lotic and lentic systems: consequences for integrated watershed management - Sachdeva, Dr. Lalit; Sehgal, Dr. Rajesh; Suyal, Ishwari Datt (International Journal of Aquatic Research and Environmental Studies, 2025)
River Corridors (RC) provide a significant share of freshwater for human and ecological requirements. The functions of flowing (lotic) rivers and creeks and ponded (lentic) waterbodies like reservoirs or lakes are extensively researched; their aggregate functions remain less comprehended. This compilation presents nationally uniform RC statistics to delineate the effects of lotic and lentic characteristics and to assess alterations over centuries prior. High-Resolution (HR) records detailing waterbodies throughout 10 million miles of the synonymous U.S. (CONUS) river network were categorized by waterway type and beginning (historic versus anthropogenic or extensively handled), area of coverage, and level of interaction, as inferred from alterations in water residence timescale within river passageways. Four decades of human disruption resulted in significant fluctuations in RC composition, with a shift towards more lotic ecosystems due to beaver disappearance and the demise of waterwheel mill lakes by the end of the 18th century. The 20th century experienced a significant increase (49%) in river passage area due to developing and maintaining small ponds and reservoirs for purposes such as hydration, hydroelectricity, water supply, livestock grazing, and stormwater drainage. The residence time of water in waterways doubled or tripled in extensive regions, and even more in particular sites, throughout the last century due to the expanded presence of shelters and monitored small lakes. Despite dams and lakes currently prevailing in the RC top areas, the findings indicate that the increasing prevalence of small ponds affects a larger segment of the system length due to their effect on headwater rivers, where most water and chemical pollution reaches the river sector. The research concludes with a framework for the integrated modelling of the tangible, biogeochemical, and biological determinants of RC operations, change paths, and governance prospects.